2002
DOI: 10.1128/iai.70.5.2414-2418.2002
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of Pregnant Dams with Intimin O157 Protects Suckling Piglets from Escherichia coli O157:H7 Infection

Abstract: Cattle are important reservoirs of enterohemorrhagic Escherichia coli (EHEC) O157:H7 that cause disease in humans. Both dairy and beef cattle are asymptomatically and sporadically infected with EHEC. Our long-term goal is to develop an effective vaccine to prevent cattle from becoming infected and transmitting EHEC O157:H7 to humans. We used passive immunization of neonatal piglets (as a surrogate model) to determine if antibodies against EHEC O157 adhesin (intimin O157 ) inhibit EHEC colonization. Pregnant sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
68
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 22 publications
0
68
0
2
Order By: Relevance
“…It is reasonable to hypothesize that antibodies directed against the structural components of the T3SS, such as EspA/B/D, or against adhesion factors, such as intimin and its cognate receptor Tir, may block bacterial binding. In support of this hypothesis, vaccination of sows with intimin has been shown to reduce the level of EHEC O157:H7 colonization of suckling piglets (24), presumably through antibody-mediated blocking of bacterial binding. In addition, bovine colostrum has been shown to reduce T3SS-mediated hemolysis in vitro (25), and passive transfer of EspB, intimin, and neutralizing antibodies against Stx2 to calves has been demonstrated following maternal vaccination (26).…”
mentioning
confidence: 71%
“…It is reasonable to hypothesize that antibodies directed against the structural components of the T3SS, such as EspA/B/D, or against adhesion factors, such as intimin and its cognate receptor Tir, may block bacterial binding. In support of this hypothesis, vaccination of sows with intimin has been shown to reduce the level of EHEC O157:H7 colonization of suckling piglets (24), presumably through antibody-mediated blocking of bacterial binding. In addition, bovine colostrum has been shown to reduce T3SS-mediated hemolysis in vitro (25), and passive transfer of EspB, intimin, and neutralizing antibodies against Stx2 to calves has been demonstrated following maternal vaccination (26).…”
mentioning
confidence: 71%
“…The results here demonstrate that the residues within EHEC intimin188 did not elicit a strong immune response when the larger fragment intimin313 was used as an immunogen. Other studies have shown that polyclonal antibodies raised against EHEC intimin282 can decrease the adherence of bacteria to HEp-2 cells (6,11). Taken together, these results suggest that antibodies capable of inhibiting bacterium-host cell interaction may well have specificities to the immunoglobulin-like domain 2 of intimin.…”
Section: Discussionmentioning
confidence: 99%
“…1921 Extensive research has been conducted on such vaccine candidates, in both murine and bovine models. These models include formulations based on recombinant expression of virulence factors, 2226 culture supernatants from virulent strains grown under conditions promoting virulence factor secretion, 27 , 28 subunits or components directly extracted from STEC strains, 2931 and heterologous expression of STEC virulence factors in both attenuated and unrelated bacteria. 32 Due to the complex mechanism responsible for colonization, it is not surprising that protection has only been observed for multi-antigenic formulations.…”
mentioning
confidence: 99%